PERAN GURU AKIDAH AKHLAK DALAM MENGATASI KENAKALAN SISWA DI MTs AL-FATAH SONGGON BANYUWANGI - Ahmad Izza Muttaqin; Fatma Sari; Shinta Aditya (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
This study focus to describe the role of aqidah moral teachers in overcoming student delinquency at MTs Al Fatah Sragi. Then the purpose of this research is to describe the steps of the Aqidah Akhlak teacher in overcoming student delinquency at MTs Al Fatah Sragi. The type of research used in this research is to use a descriptive qualitative approach, while the data collection procedure uses three techniques, namely observation, interviews, and documentation. The process of data analysis through data reduction, data presentation, and conclusions. Then to check the validity of the data using source triangulation. Based on the results of the study it was found that the teacher of the moral creed has a role as an educator. The role of the moral creed teacher as an educator is to train attitudes and mentality by giving responsibility, setting an example by giving an example of how to look neat, speak politely and be kind, building an open attitude by maintaining good communication with students, cultivate the nature of discipline by making rules in the classroom with penalties if students violate them, providing moral values ​​by making habituations such as getting used to practicing good morals. While the steps taken by the teacher of aqidah morals in dealing with student delinquency are conducting supervision of students, routine guidance and counseling for students, and special approaches to children who are already showing symptoms of delinquency.